Perubahan Struktur Konseptual Mahasiswa Pendidikan Biologi tentang Morfologi Daun dan Bunga berdasarkan Pictorial Representation - Sariwulan Diana; Puti Siswandari; Tri Suwandi; Amprasto Amprasto (Universitas Sebelas Maret, 2025)
Observation skills in biology can be assessed through pictorial representation, which involves asking students to create drawings and add annotations to explain the observed objects. This technique provides insight into students' perceptions and conceptual understanding of biological objects. This study aims to identify students' conceptual changes regarding leaf and flower structures based on a pictorial representation test. This descriptive research involved 35 second-semester students from the Biology Education Program at the Indonesia University of Education, who enrolled in the Plant Morphology course in the even semester of the 2023/2024 academic year. The pictorial representation test was conducted for 15 minutes before and after the lectures (pre-test and post-test) using the inquiry learning model, focusing specifically on leaf and flower structure topics. The test results were evaluated by two lecturers using a mutually agreed-upon scoring guide. The data were analyzed descriptively using a conceptual change scheme from pre-test to post-test. The results showed that there were four patterns of conceptual structure changes identified from pictorial representation of leaf and flower morphology, namely: construction, static, revision, and complementation, while the disorientation pattern was only found in the pictorial representation of flower morphology. Almost half of the students (48.6%) experienced changes in conceptual structure with construction patterns in leaf and flower morphology content. The most dominant final category of concept mastery is good, which is 51.4% and 48.6%, respectively in leaf and flower morphology. In flower morphology, there was a greater increase in the very good category compared to leaf morphology, with a ratio of 25.7% and 14.3%. Apart from a number of students whose concept mastery did not change significantly (static) and one case of disorientation on the concept of flower morphology. Overall, the conceptual change scheme based on pictorial representation results can help to analyze the extent to which learning can improve concept mastery of leaf and flower morphology.